Chemical induction of sterility in thermosensitive genic male sterile rice (Oryza sativa)* - VIJAYALAKSHMI, D; BANGARUSAMY, U (The Indian Journal of Agricultural Sciences, 2011)
An attempt was made to identify a suitable chemical that can induce complete sterility in a thermosensitive genic male sterile rice line (Oryza sativa L.) even when the temperature drops below the critical sterility temperature. During the sensitive phase ofpanicle development, salicylic acid @800 ppm and 1000 ppm andethrel 800 ppm were sprayed at third and fifth stages of panicle development. Salicylic acid spray at 800 ppm concentration caused near complete ponen sterility in ’TS 29’. Salicylic acid was found to be the best and lowpriced alternative to ethrel in inducing pollen sterility without affecting the female fertility. The effect of salicylic acid is attributed to the increase in body temperature of the plant in induction ofsterility. Salicylic acid treatments recorded higher seed set percentages compared to ethrel treatment, it appeared that, ethrel affected the female organs to a certain extent in addition to effecting pollen sterility.